A new species, Lasioglossum (Eickwortia) hienae, from Mexico (Apoidea: Halictidae) - Gibbs, Jason; Dumesh, Sheila (Journal of Melittology, 2013)
A new species from Colima, Mexico, Lasioglossum (Eickwortia) hienae Gibbs & Dumesh, new species, is described and illustrated. Lasioglossum hienae is distinguished from related species based on a combination of morphological, geographical, and molecular evidence. A species distribution model is used to predict the potential distribution of the known species of L. (Eickwortia). An identification key is provided.